2016
DOI: 10.1128/mcb.00174-16
|View full text |Cite
|
Sign up to set email alerts
|

SCFFbl12 Increases p21Waf1/Cip1 Expression Level through Atypical Ubiquitin Chain Synthesis

Abstract: The cyclin-dependent kinase (CDK) inhibitor p21 is an unstructured protein regulated by multiple turnover pathways. p21 abundance is tightly regulated, and its defect causes tumor development. However, the mechanisms that underlie the control of p21 level are not fully understood. Here, we report a novel mechanism by which a component of the SCF ubiquitin ligase, Fbl12, augments p21 via the formation of atypical ubiquitin chains. We found that Fbl12 binds and ubiquitinates p21. Unexpectedly, Fbl12 increases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…We used these ubiquitin probes to analyze the ubiquitination of PAF15 (mono-Ub) 38, 39 , DNMT3A (K63-Ub) 46 , p21 (K48- and K63-Ub) 47, 48 , Cyclin B1 (K11-Ub) 49 , p53 (K48-Ub) 50 and H2A (mono-and K63-Ub) 51, 52 (Fig. 3C, Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used these ubiquitin probes to analyze the ubiquitination of PAF15 (mono-Ub) 38, 39 , DNMT3A (K63-Ub) 46 , p21 (K48- and K63-Ub) 47, 48 , Cyclin B1 (K11-Ub) 49 , p53 (K48-Ub) 50 and H2A (mono-and K63-Ub) 51, 52 (Fig. 3C, Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports also have identified UBE2L3 as catalyzing the conjugation of p27Kip1 to heterogeneous ubiquitin chains and protecting them from degradation [ 54 ]. RNF4 forms K11/K33 ubiquitin chain conjugates of β-catenin that inhibit degradation [ 55 ], and SCFFbl12 forms K48/K63 ubiquitin chains inhibiting degradation of p21 Cip1/Waf1 [ 56 ]. Here we found that UBE2L6 inhibits the degradation of SVA 3D by catalyzing the K48/K63 mixed chains.…”
Section: Discussionmentioning
confidence: 99%
“…Usp15 was amplified from the cDNA clone from the Kazusa DNA Research Institute and inserted into pcDNA3-Flag and pcDNA3-Myc vectors. The pCAGEN-His-Ub (wild-type and mutants) construct was described previously (57).…”
Section: Methodsmentioning
confidence: 99%